METHODOLOGIES TO MITIGATE ATTENUATING EFFECTS IN FLARE GAS FLOW MEASUREMENT BY ULTRASONIC TECHNOLOGY AT LOW PRESSURE AND HIGH CARBON DIOXIDE CONCENTRATION - Franco, Ligia Gaigher (2020)
Worldwide, hydrocarbon flow measurement is governed by regulations. It is well known in literature that CO2 strongly attenuates wave generated by ultrasonic flow meters, which is the technology most used in flare gas application. In this context, this wor